2019
DOI: 10.1371/journal.pone.0220203
|View full text |Cite
|
Sign up to set email alerts
|

The cresty neck score is an independent predictor of insulin dysregulation in ponies

Abstract: Generalized obesity, regional adiposity, hyperinsulinemia and hypertriglyceridemia are all potential indicators of equine metabolic syndrome (EMS). This study aimed to assess the relationship between morphometric measurements of body condition and metabolic hormone concentrations in ponies, with and without a neck crest or generalised obesity. Twenty-six ponies were assigned a body condition score (BCS) and cresty neck score (CNS). Height, girth, and neck measurements were taken. An oral glucose test (OGT; 0.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 50 publications
4
32
3
Order By: Relevance
“…However, in that study laminitis was induced with diet and therefore the risk factors may not have been the same as those in naturally occurring cases 41 . On the other hand, HMW adiponectin has been shown to correlate negatively with both basal 21 and postprandial insulin, 42 and in our study, decreasing adiponectin was a significant risk factor for increased InsMax after OST. Additionally, adiponectin was significantly lower in ID horses vs. non‐ID horses.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…However, in that study laminitis was induced with diet and therefore the risk factors may not have been the same as those in naturally occurring cases 41 . On the other hand, HMW adiponectin has been shown to correlate negatively with both basal 21 and postprandial insulin, 42 and in our study, decreasing adiponectin was a significant risk factor for increased InsMax after OST. Additionally, adiponectin was significantly lower in ID horses vs. non‐ID horses.…”
Section: Discussioncontrasting
confidence: 49%
“…Similar findings have been observed in a previous study where postprandial insulin concentration was positively associated with CNS, and ponies with a CNS ≥3 had five times greater odds of having ID. 42 Additionally, it was suggested that CNS would be more predictive of ID than BCS. In the present study, CNS and BCS were the same between the ID groups, but ID horses had a longer neck circumference than non-ID horses.…”
Section: Discussionmentioning
confidence: 99%
“…The causal relationship between obesity and EMS remains unclear, but a proinflammatory state 28 and dysregulation of adipokines, for example adiponectin and leptin 3 , 13 are likely. An association between BCS and ID has been lacking in some smaller experimental studies, 29 while others have demonstrated an effect of diet 30 or regional adiposity. 2 , 29 Although BCS is an imperfect predictor of total body fat 31 these results support its use as a modifiable risk factor and to screen for animals at increased risk of EMS.…”
Section: Discussionmentioning
confidence: 99%
“…An association between BCS and ID has been lacking in some smaller experimental studies, 29 while others have demonstrated an effect of diet 30 or regional adiposity. 2 , 29 Although BCS is an imperfect predictor of total body fat 31 these results support its use as a modifiable risk factor and to screen for animals at increased risk of EMS.…”
Section: Discussionmentioning
confidence: 99%
“…Horses with identifiable causes of laminitis other than HAL, such as colic or sepsis, were excluded from the study. Evidence of ID, consistent with HAL, included at least one of the following conditions: a high body condition score (≥ 4/5 on the Carroll and Huntingdon scale) [ 26 ], fat in specific sites such as the nuchal crest [ 27 ], a previous diagnosis of insulin dysregulation according to basal insulin concentrations or dynamic testing, and/or a diagnosis of Pituitary Pars Intermedia Dysfunction (PPID). Horses with PPID were only included if they were either untreated (and remained so), or received a constant dose of pergolide for at least 6 weeks prior to the study, and were maintained on the drug throughout the study.…”
Section: Methodsmentioning
confidence: 99%